Quantifying Benthic Flux of Mysis Biomass Through Diel Vertical Migration at the Ecosystem Scale - Brian P. O’Malley; Georgia W. Hoffman; Rosaura J. Chapina; Jason D. Stockwell; Collin J. Farrell (Ecosystems, 2025)
Mysis diluviana is a macroinvertebrate that couples benthic and pelagic habitats on a daily timescale through diel vertical migration (DVM). However, quantifying how much Mysis biomass is exchanged between benthic and pelagic habitats at an ecosystem scale is difficult because of sampling limitations and variability in Mysis DVM behavior related to light and depth. Although Mysis are benthic-pelagic migrators, a portion remains pelagic during the day offshore in Lake Ontario, partially contradicting the assumption of population-level DVM over deep areas. To estimate the amount of biomass transferred from benthic to pelagic habitat via DVM in Lake Ontario, we estimated the portion of pelagic biomass at night originating from benthic habitat as the difference between night and day pelagic estimates from net tows along a bathymetric depth gradient. We then modeled the portion as a function of depth, extrapolated these depth-dependent estimates to an existing lake wide night-pelagic dataset, and summed amounts across depth strata. We estimated more biomass was transferred from benthic to pelagic habitat at intermediate lake depths (100–160 m) despite greater offshore (> 180 m) night-pelagic biomass. Our results suggest ways to improve estimates of Mysis habitat coupling and how to account for important factors such as depth and light for modeling Mysis DVM behavior at the population- and ecosystem-levels.